Capital Expenditure Application Of Real Options Approach - Mollagholamali, Mohsen (2008)
The main purpose of this project is to provide a simple yet efficient framework for managers to make decisions in an uncertain environment and enjoy the luxury of flexibility. Among all the option valuation methods available to managers, thebinomial alttice (risk-neutral probability approach) tends to be the most efficient and user-freindly way to value investments in real assets.